(untitled) (European Journal of Pure and Applied Mathematics, 2023)
The complex dynamical analysis of the cubic-order iterative family is proposed to draw the fractal images via Möbius conjugacy map applied to a quadratic polynomial (z-A) (z-B). The resulting dynamics is clearly visualized through various stability surfaces and parameter spaces using Mathematica.